The prevalence of low health literacy in undergraduate students in Pakistan. (1st February 2023) - Rehman, Aziz‐ur; Bin Naeem, Salman; Faiola, Anthony
Abstract: This Regular Feature is based on a PhD study assessing the level of health literacy among university students in Pakistan. A cross‐sectional survey was carried out using the validated European Health Literacy Survey (HLS‐EU‐Q) and non‐parametric tests used to analyse data with the aim of determining the influence of personal determinants on health literacy skills. The findings of the study concluded that the population had a low health literacy level with limited skills in accessing, understanding, appraising and applying information for health care. Gender, age, and native languages, all had a statistically significant influence on health literacy skills. Practical implications are presented for the role of university libraries in supporting the development of health literacy in their undergraduate student populations are presented, including the need for the provision of health information in native languages.